TAX FRAUD AS A SUBJECT OF FORENSIC ECONOMIC EXPERTISE - Антышева, Елена; Терновская, Маргарита (SWorldJournal, 2021)
The article analyzes the existing system of offenses in the tax sphere. The main articles on which fraudsters are involved for this offense are considered. The approaches to choosing the correct punishment for the committed act, as well as the types of s